Las imágenes de los santuarios de Cástulo: Los exvotos ibéricos en bronce de Collado de los Jardines (Santa Elena) y los Altos del Sotillo (Castellar) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The votive offerings bronzes of the iberian sanctuaries of “Collado de los Jardines” and “Los Altos del Sotillo” are one of the most representative iconographic manifestations of the Oretanean’s ideology. In this work we analyzed their role as symbolic landscape milestones and ideological projections of the territory of Cástulo, associated with a socio- political process documented in the High Guadalquivir from beginnings of the 4th century B.C.
Keywords: Bronze Exvotes; Sanctuaries; High Guadalquivir; Image; Cástulo